Persepsi Pengunjung Joglo Tani Sebagai Agroedukasi Sistem Pertanian Terpadu - Pratama, Firza Zidan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Agroeducation is presented as a form of developing a sustainable concept of agrotourism. Agroeducation is a step to combine the concepts of tourism, agriculture and education in one place with tourism activities that make agriculture the object. Joglo Tani is one of the agroeducations that implements an integrated agricultural system that has not been widely implemented in Indonesia. The existence of Joglo Tani with various activities offered as agroeducation certainly provides an attraction for visitors to visit Joglo Tani where visitors who attend provide different perceptions regarding the existence of Joglo Tani, where perception is very important for the development and existence of Joglo Tani itself. This study aims to determine the perception of visitors to Joglo Tani as an integrated agricultural system agroeducation and to analyze factors related to the perception of visitors to Joglo Tani as an integrated agricultural system agroeducation. Respondents were determined by accidental sampling of 50 visitors as respondents. By using questionnaires and interviews in obtaining data. The data were analyzed using a quantitative descriptive method with a scoring technique using a Likert scale and Spearman rank correlation analysis to determine related factors. The results of the study showed that the perception of visitors to Joglo Tani as an integrated agricultural system agro-education had a score of 4.20 with a good category. The results of the Spearman rank correlation coefficient analysis showed that the factors related to the perception of visitors to Joglo Tani as a whole were facilities, services, accessibility and promotion.